Unusual Course of Scimitar Syndrome Preceded by Lung Hypoplasia - Yusuke Hoshino; Junichi Arai (Case Reports in Pediatrics)
In patients with Scimitar syndrome, right pulmonary artery hypoplasia is considered to lead to right lung hypoplasia because of decrease in blood flow. However, there are no reports wherein the change was actually detected. Thus, the exact developmental mechanism of right pulmonary artery hypoplasia and right lung hypoplasia in patients with Scimitar syndrome is unclear. We experienced a case of Scimitar syndrome preceding right lung hypoplasia, and right pulmonary artery hypoplasia gradually revealed with time. We hypothesized that, in our patient, the lung hypoplasia led to pulmonary artery hypoplasia due to decrease in blood flow. If there are no differences in the diameter of the left and right pulmonary artery in patients with Scimitar syndrome at birth, we propose the necessity of careful observation due to the possibility that pulmonary artery hypoplasia may develop in the future.